Model Dispersi Gas dan Vapor Cloud Explosion pada Kebocoran Outlet Pigtail Tubes Primary Reformer - Perwitasari Perwitasari; Sumardi Sumardi; Indra Perdana (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2018)
Outlet pigtail tubes, one of the components in primary reformer, have a function to carry the reformed gas from the catalyst tubes to the collection manifold. Moreover, it also has a function to provide the required flexibility within the system to avoid overstress at the end of connections of the pigtail to the manifold and to the bottom of the catalyst tube. It operates in an extreme condition with temperature range of 825-850 oC and pressure 36.2 kg/cm2 which is possible to initiate a failure. The consequences of outlet pigtail tubes failure are a dispersion of synthesis gas and vapor cloud explosion. This research aimed to make a model of those consequences with an assumption that the leakage hole was the same as the diameter of outlet pigtail tubes. The gas dispersion model used in this research was dense gas dispersion continuous release model. The results showed that the highest ratio of synthesis gas-air concentration was 0.1 at 17.4 m distance from leaking point. Whereas the lowest ratio of synthesis gas-air concentration was 0.002 at 163.4 m distance from leaking point. The highest ratio of the concentration of gas dispersion gave vapor cloud explosion energy of about 11.67 x 105 kJ with an overpressure of about 8.41 kPa. The overpressure caused a partial demolition of the building (for example control room), panels blow in, and fastening fails of equipment or machines around the area. A B S T R A KOutlet pigtail tubes adalah salah satu komponen pada primary reformer yang berfungsi untuk membawa gas hasil reforming dari tube katalis ke manifold. Selain itu outlet pigtail tubes juga berfungsi untuk memberikan fleksibilitas yang diperlukan di dalam sistem sehingga terhindar dari overstress di bagian akhir sambungan antara pigtail dengan manifold dan bagian bawah dari tube katalis. Outlet pigtail tubes beroperasi pada kondisi ekstrim yaitu suhu 825-850 oC dan tekanan 36,2 kg/cm2 yang mana memungkinkan untuk terjadinya kegagalan. Konsekuensi dari kegagalan outlet pigtail tubes adalah dispersi gas sintesis dan ledakan awan uap. Penelitian ini bertujuan untuk membuat model dari konsekuensi tersebut dengan asumsi bahwa lubang kebocoran sama dengan diameter outlet pigtail tubes. Model dispersi gas yang digunakan dalam penelitian ini adalah model dispersi dense gas untuk pengeluaran yang kontinu. Hasil menunjukkan bahwa rasio konsentrasi gas sintesis-udara tertinggi adalah 0,1 pada jarak 17,4 meter, sedangkan rasio konsentrasi terendah adalah 0,002 pada jarak 163,4 meter. Konsentrasi tertinggi dari gas terdispersi memberikan energi untuk ledakan awan uap sebesar 11,67 x 105 kJ dengan overpressure sebesar 8,41 kPa. Overpressure tersebut menyebabkan kerusakan pada sebagian dari bangunan (sebagai contoh ruang kontrol), terlemparnya papan, dan mempercepat kegagalan dari peralatan atau mesin di sekitar area.